Flow injection amperometric determination of procaine in pharmaceutical formulation using a screen-printed carbon electrode - Bergamini, Marcio F.; Santos, Andre L.; Stradiotto, Nelson Ramos [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V., 2007)
A rapid and simple method for procaine determination was developed by flow injection analysis (FIA) using a screen-printed carbon electrode (SPCE) as amperometric detector. The present method is based on the amine/hydroxylamine oxidation from procaine monitored at 0.80 V on SPCE in sodium acetate solution pH 6.0. Using the best experimental conditions assigned as: pH 6.0, flow rate of 3.8 mL min(-1), sample volume of 100 mu L and analytical path of 30 cm it is possible to construct a linear calibration curve from 9.0 x 10(-6) to 1.0 x 10(-4) mol L-1. The relative standard deviation for 5.0 x 10(-5) mol L-1 procaine (15 repetitions using the same electrode) is 3.2% and detection limit calculated is 6.0 x 10(-6) mol L-1. Recoveries obtained for procaine gave a mean values from 94.8 to 102.3% and an analytical frequency of 36 injections per hour was achieved. The method was successfully applied for the determination of procaine in pharmaceutical formulation without any pre-treatment, which are in good accordance with the declared values of manufacturer and an official method based on spectrophotometric analysis. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: procaine; FIA amperometric; screen-printed carbon electrode